Microbial community structure and potential functional diversity in a post-mining ecosystem of central China - Xu, Quan; Tan, Donghua; Liu, Jingqi; Qiu, Huangfeng; Yang, Yu (Frontiers in Environmental Science, 2025)
Abandoned coal mines cause severe soil degradation, water pollution, and biodiversity loss. This study characterizes microbial community dynamics across distinct microhabitats—slag-enriched soil (D-1), waterlogged sediment (W-3), and acidic wastewater (W-5)—in Hunan mining areas. High-throughput 16S rRNA sequencing revealed Proteobacteria (31%–60%) dominance across sites, with Firmicutes enriched in acidic W-5 (49%) and Bacteroidetes in organic-rich D-1 (21%). Community diversity significantly diverged along pH/metal gradients (db-RDA: pH explained 74.8% variation, p < 0.001), correlating with environmental stressors. Functional predictions (PICRUSt/FAPROTAX) suggest potential adaptations: sulfur oxidation increased in acidic zones (25.7%), while organic degradation peaked in contaminated soils (38.1%). These community-environment linkages support bioremediation design: augmenting acid-tolerant taxa in low-pH zones and pollutant-degrading microbes in metal-impacted soils to accelerate ecological restoration.